Local efforts and people participation in the development of marginal regions : a summary of 10 years' research at the Fribourg Department of Geography - Leimgruber, Walter (1995)
The present paper offers an overview of research on development in Third World countries done by researchers of the Department of Geography of Fribourg University (Switzerland) over the past 10'years. The common denominator of all the projects reportad is the focus on the local/regional scale, on people and their needs, on their potential for endogenous development. Most of the research has been carried out in French speaking West Africa, in particular in Burkina Faso (formerly Upper Volta) where rural development strategies have been (and are still being) examined. It is planned to transfer this focus on autochtonous development efforts to developed countries: Third World countries are marginal áreas on a woridwide scale, but similar problems of marginality are increasingly found in the 'North', and here, too, endogenous potentials may be important for local/regional survival.